PENINGKATKAN KINERJA GURU MELALUI SUPERVISI KEPALA SEKOLAH DI SMP NEGERI 7 SIMPANG HILIR - Megawati, Megawati; Wicaksono, Luhur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to describe the planning, implementation, results, and obstacles in the clinical supervision of principals at SMP Negeri 7 Simpang Hilir. This study uses a qualitative method which was carried out in March-May 2022. The subjects of this study were (1) Deputy principals, and (2) Teachers at SMP Negeri 7 Simpang Hilir. Data acquisition by means of; observation, interview and documentation. The results of this study indicate that: (1) The planning and implementation of principal supervision at SMP Negeri 7 Simpang Hilir has been carried out effectively. (2) the performance of teachers at SMP Negeri 7 Simpang Hilir has increased significantly. (3) the supervision carried out by the principal has a positive influence on the performance of teachers at SMP Negeri 7 Simpang Hilir. This research is also to determine whether there are deviations in the implementation of learning accompanied by improvement efforts and supervision is carried out on an ongoing basis so as to ensure that learning activities are carried out in real terms and are planned activities.